2014
DOI: 10.4103/0971-6203.131279
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of MLC fields for cobalt therapy machine

Abstract: An automated Multi-Leaf Collimator (MLC) system has been developed as add-on for the cobalt-60 teletherapy machines available in India. The goal of the present computational study is to validate the MLC design using Monte Carlo (MC) modeling. The study was based on the Kirloskar-supplied Phoenix model machines that closely match the Atomic Energy of Canada Limited (AECL) theratron-80 machine. The MLC is a retrofit attachment to the collimator assembly, with 14 non-divergent leaf pairs of 40 mm thick, 7 mm wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…The design and radiation characteristic study of prototype MLCs were presented in conferences[ 2 3 4 ] and reported. [ 32 ] It has been previously[ 33 ] demonstrated that the designed MLCs can be successfully used for conformal therapy. Due to intensive use of multi-leaf collimators (MLCs) in clinics, it is important to find an optimum design for the leaves.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The design and radiation characteristic study of prototype MLCs were presented in conferences[ 2 3 4 ] and reported. [ 32 ] It has been previously[ 33 ] demonstrated that the designed MLCs can be successfully used for conformal therapy. Due to intensive use of multi-leaf collimators (MLCs) in clinics, it is important to find an optimum design for the leaves.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The design and radiation characteristic study of prototype-1 MLCs were presented in conferences [ 8 - 10 ] and reported [ 5 , 11 ]. For both the prototypes 1 and 2, the material used was tungsten alloy with density of 18 g/cm 3 (W 95% + Ni 3.5% + Cu 1.5%).…”
Section: Methodsmentioning
confidence: 99%
“…The Monte Carlo (MC) simulations were carried out using the same machine specifications which were explained in detail in our previous simulations as well [ 11 ]. The MLC leaves were opened to 6 × 6 cm 2 square field with the collimator jaws wide open.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive tests were performed to verify the correction and accuracy of data collection and machine modeling according to the AAPM report TG‐53. In addition, ROPS has been tested using certain measurements and Monte Carlo calculations for cobalt‐60 fields (15) . The details of ROPS specifications can be found from the website at https://sites.google.com/site/tjcsrops.…”
Section: Methodsmentioning
confidence: 99%